Aerosol Characterization and Direct Radiative Forcing Assessment over the Ocean. Part II: Application to Test Cases and Validation - Costa, Maria João (2012)
A method based on the synergistic use of low earth orbit and geostationary earth orbit satellite data for aerosoltype characterization and aerosol optical thickness (AOT: ta) retrieval and monitoring over the ocean is presented in Part I of this paper. The method is now applied to a strong dust outbreak over the Atlantic Ocean in June 1997 and to two other relevant transport events of biomass burning and desert dust aerosol that occurred in 2000 over the Atlantic and Indian Oceans, respectively. The retrievals of the aerosol optical properties are checked against retrievals from sun and sky radiance measurements from the ground-based Aerosol Robotic Network (AERONET). The single-scattering albedo values obtained from AERONET are always within the error bars presented for Global Ozone Monitoring Experiment (GOME) retrievals, resulting in differences lower than 0.041. The retrieved AOT values are compared with the independent space–time-collocated measurements from the AERONET, as well as to the satellite aerosol official products of the Polarization and Directionality of the Earth Reflectances (POLDER) and the Moderate Resolution Imaging Spectroradiometer (MODIS). A first estimate of the AOT accuracy derived from comparisons with AERONET data leads to 60.02 6 0.22ta when all AOT values are retained or to 60.02 6 0.16ta for aerosol transport events (AOT . 0.4). The upwelling flux at the top of the atmosphere (TOA) was computed with radiative transfer calculations and used to estimate the TOA direct shortwave aerosol radiative forcing; a comparison with space–time-collocated measurements from the Clouds and the Earth’s Radiant Energy System (CERES) TOA flux product was also done. It was found that more than 90% of the values differ from CERES fluxes by less than 615%.